Efficacy of chemical disinfectant compounds against human norovirus. (January 2016) - Ha, Ji-Hyoung; Choi, Changsun; Lee, Hee-Jung; Ju, In-Sun; Lee, Jeong-Su; Ha, Sang-Do
Abstract: The purpose of this study was to evaluate the efficacy of various disinfectant compounds against human norovirus (NoV). We investigated the disinfection effects of ethanol, sodium hypochlorite, hydrogen peroxide, quaternary ammonium compounds, and iodine using an anti-NoV GII.4 monoclonal antibody-conjugated immuno-magnetic separation (IMS) technique combined with quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR). Ten-minute treatments of samples containing NoV GII.4 with 10–70% ethanol resulted in mean log10 reductions in genomic copies/μL of less than 1. In contrast, 10-min treatments with sodium hypochlorite at 200, 500, and 1000 ppm resulted in mean log10 reductions of 1.55, 1.85, and 2.45, respectively; however, 50 and 100 ppm sodium hypochlorite had no disinfection effect, as shown by the log10 reductions of less than 1. Treatment with hydrogen peroxide (200–1000 ppm), quaternary ammonium compounds (100–2000 ppm), and iodine (25–500 ppm), also exhibited no disinfection effect. The results of this study show that NoV GII.4 is remarkably resistant to most disinfectants and suggests that new disinfectant compounds are needed to inactivate foodborne bacteria and viruses, especially NoV GII.4. Highlights: Treatment of NoV GII.4 with 10–70% ethanol achieved a mean log10 reduction of <1. H2 O2 (≤1000 ppm), quaternary ammonium (≤2000 ppm), and iodine (≤500 ppm) exhibited no disinfection effect. NaOCl at 200, 500, and 1000 ppm reduced NoV GII.4 by 1.55, 1.85, and 2.45, respectively.